THE PERCEPTION OF ALAY SUBCULTURE TOWARD KOREAN NATION BRANDING (K-WAVE) - Hanny Purnama Sari (Perpustakaan Universitas Surabaya, 2016)
South Korea is one of a country that has a good image overseas due to the successful of their nation branding. With K-Wave as their nation branding they introduce their country and culture through Korean entertainment. Indonesia is one of Asian countries which also really exposed by the Korean Wave, especially Alay subculture. The fact that Korean Wave affecting the behavior and way of thinking in Indonesian society especially Alay subculture became an interesting phenomenon to study. This study have the purpose to explore the phenomenon and trying to figure the perception of Alay subculture toward Korean nation branding (Korean Wave) and what factors that influence the Alayers’ perception process. Using consumer perception theory, the researchers try to analyze and elaborate each stage of perception process that Alayers experienced. The knowledge of this research may be beneficial towards government especially to Indonesian government to create a great and successful nation branding for Indonesia. Also the researcher expects to reveal the answer that will create a clear explanation of the phenomenon for this issue.